Peran Kemandirian Belajar dalam Memediasi Pengaruh Keterlibatan Orang Tua terhadap Hasil Belajar Siswa SMA Khadijah Surabaya - Mohamad Arief Rafsanjani; Nabila, Nabila Nur 'Aini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study was conducted to analyze the effect of parental involvement and learning independence on student learning outcomes. This type of research uses a quantitative approach. The subjects of this study were X and XI grade students of Khadijah Surabaya High School as many as 158 students who were taken as samples using proportionate stratified random sampling method. Data were collected using questionnaires and documentation. The data analysis technique used was Structural Equation Modeling (SEM) using WarpPLS software. The results of this study indicate that there is an effect of parental involvement on learning outcomes, learning independence has no effect on learning outcomes, parental involvement affects learning independence, learning independence does not mediate the effect of parental involvement on learning outcomes.